Physiopathology and biomechanics of hip osteoarthritis - Frosi, G.; Sulli, A.; Testa, M.; Cutolo, M. (Reumatismo, 2001)
Several factors seem to play a relevant role in the pathogenesis of hip osteoarthritis. Among these, an altered biomechanic and neuromuscular integrity of the hip joint should be considered. This is a review of the recent international literature concerning the role of loads and strengths acting on the hip joint, in order to better understand the pathogenesis and the physiopathology of the hip osteoarthritis. The study of these factors might be important to prevent the development of the osteoarthritis and might suggest the conservative treatment. In particular, the role of the balance among the muscles working in maintaining the equilibrium of the acting strengths is matter of discussion. The articular and neuromuscular dysfunction might induce an altered load distribution in the hip, particularly on the articular cartilage surface, and seems to favour the development of hip osteoarthritis...